Technical principles of "Atemi-waza" in the first technique of the "Itsutsu-no-kata" in Judo: From a view point of Jujutsu-like "Atemi-waza" - Shishida, F.; Sakaguchi, M.; Sato, T.; Kawakami, Y. (Sport Science Research, 2015)
The purpose of this study is to clarify the following three points, based on Kenji Tomiki`s theory, who pointed out properly that the Atemi-waza (striking technique) is, in principle, an extension of Nagewaza (throwing technique). (1) To analyze the most relevant previous studies, in terms of technique, written by Sumiyuki Kotani & Tadao Otaki, chosen among the seven previous studies which describe the teachings of the first technique of the Itsutsu-no-kata (forms of five), advocated by Jigoro Kano. (2) To demonstrate the first technique of the Itsutsu-no-kata, based on the interpretation by Tomiki, who referred, earlier on, to the unique relationship between the first technique of the Itsutsu-nokata and the Atemi-waza, and to analyze its video image in terms of technique and biomechanics. (3) To clarify the technical principles of the Atemi-waza in Jujutsu by synthesizing both of the above mentioned, namely the first technique of the Itsutsu-no-kata and the Atemi-waza.